2023
DOI: 10.3991/ijet.v18i11.38637
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mobile Application-Assisted Instruction on Intrinsic Motivation and Sports Nutrition Knowledge: The Case of Blended Learning

Aseel O. Ajlouni,
Walaa Jumah AlKasasbeh,
Arene Al-Shara'h
et al.

Abstract: Abstract— In the physical education literature, E-learning in terms of online or blended learning has been lacking and facing several challenges which highlighted a need to conduct more research to investigate modern instruction in the context of physical education. This study is one of the few to determine the impact of Mobile Application-Assisted Instruction (MAAI) on intrinsic motivation and sports nutrition knowledge in a blended learning setting. The “KI-coach” app has been used as a state of an art mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 82 publications
0
3
1
Order By: Relevance
“…This result does not align with the research results, which revealed that the utilization of the mobile app enhanced the learning IM of undergraduate students [76]- [78]. It is possible that additional elements could be incorporated into the app to enhance motivation.…”
Section: Effectiveness Of Using Mobile Learning App With Online Nutri...contrasting
confidence: 74%
“…This result does not align with the research results, which revealed that the utilization of the mobile app enhanced the learning IM of undergraduate students [76]- [78]. It is possible that additional elements could be incorporated into the app to enhance motivation.…”
Section: Effectiveness Of Using Mobile Learning App With Online Nutri...contrasting
confidence: 74%
“…This can contribute to the digital transformation of education, enhancing the learning experience for students in STEAM fields. By proper organizational leadership [87], taking future considerations into developing augmented learning environments to engage students reasoning [88], mental intelligence [89], and healthy lifestyles [90].…”
Section: Future Research Guidelines and Applicationsmentioning
confidence: 99%
“…Technology has become increasingly important in education [15], [16], and through its incorporation, students are evolving within a data-driven, digitalized learning environment [17], It offers a learning environment that fosters genuine learning experiences, creates a conducive setting for achieving desired learning goals [18], and promotes a more positive approach to knowledge discovery and review while emphasizing the pivotal role of students [19]. Its application within the context of PE is not as well-documented or understood.…”
Section: Introductionmentioning
confidence: 99%